Penilaian Livability Perumahan Subsidi bagi Masyarakat Berpenghasilan Rendah di Kota Ambon - Wa Ode Sitti Jurianti Aswad; Hertine Megiestri Kesaulya; Resky Prafitri (Jurnal Syntax Admiration, 2024)
Subsidized housing is one of the main programs to provide livable housing that is affordable for low-income communities. However, often in development and environmental management, livability aspects are not paid attention to which can affect the level of community comfort and the quality of the housing itself. This condition can be seen in Bukit Hijau Urimessing Housing, which is currently the only subsidized housing in Ambon City. The condition of infrastructure and facilities such as roads, waste facilities and accessibility are still inadequate. The aim of this research is to measure the level of livability of Bukit Hijau Urimessing Housing, which is based on aspects of housing livability. This research uses a quantitative approach with quantitative descriptive analysis techniques and scoring analysis methods on 11 (eleven) housing livability indicators. The results of the analysis show that there are 5 (five) aspects with a level of livability included in the low category, namely the availability/quality of residential roads, access to transportation services, waste, drainage networks and security and safety of the residential environment. This condition reinforces the problems that often occur in the construction of subsidized housing, namely related to facility readiness, location not paying attention to accessibility and environmental management that is not optimalt.